Toxic effect of volatiles from Callistemon lanceolatus on six fungal pathogens of rice - and S.N. TEWARI, DEBJANI MISRA, MANASI MISRA (Indian Phytopathology, 2002)
The essential oil from C. lanceolatus [C. citrinus] was tested against Magnaporthe grisea, Rhizoctonia solani, Fusarium moniliforme [Gibberella fujikuroi], Curvularia lunata [Cochliobolus lunatus], Aspergillus flavus and A. niger. The min. inhibitory concentration of spore germination was 3000 p.p.m. against M. grisea. Concentrations of 8000 p.p.m. inhibited mycelial growth of all the pathogens, except R. solani.